Pengaruh Penerapan Sistem Automatic Exchange Of Information, Sistem Administrasi Modern, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak - Dwi Fionasari; Retri Wiyarni; Della Hilia Anriva; Annie Mustika Putri; Norra Isnasia Rahayu (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study aims to test whether there is an influence between automatic exchange of information system, modern administration system, and tax sanctions on taxpayer compliance. The data used in this study are primary data. This type of research is quantitative. The object of this research is the tax employee of the account representative division at the pratama service tax office Pekanbaru city, namely KPP Pratama Senapelan, KPP Pratama Tampan, and KPP Madya Pekanbaru city. Sample collection method using saturated sample method. Samples taken are 83 people. Test data analysis using multiple linear regression method processing using SPSS 20. The result of this study indicate that the automatic exchange of information system affects taxpayer compliance, while the modern administration sytem and tax sanctions have no effect on taxpayer compliance.